Studi Mengenai Karakter Kreatif Guru PPKn di SMK Negeri 2 Kota Serang - Citra, Anita Permata; Ratna Sari Dewi; Reza Mauldy Raharja (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
The obstacles faced by Civics teachers regarding creative character are the inappropriate selection of teacher learning methods that are less creative so that students lack interest in participating in learning. The type of research used in this research is qualitative research. This research seeks to describe or describe what was researched regarding the creative character of Civics teachers. In this study the authors used three data collection techniques including observation, interviews, documentation which are expected to support the problems studied by the author regarding the creative character of Civics teachers at SMK Negeri 2 Serang City. Based on the findings, it is found that being a creative teacher is required to have the ability to develop approaches, strategies, use learning media and choose effective and conducive learning methods and master various teaching skills. A creative teacher can foster enthusiasm for learning to students by teaching in a unique and fun way to make students interested in learning by using various methods and learning media. In addition, teachers must provide a conducive and non-monotonous classroom learning atmosphere that makes learning more advanced by creating learning trying new things to create various models or methods and learning media and to meet the needs of students. In the use of appropriate and creative learning methods can affect the effectiveness of the learning process.